2023
DOI: 10.3390/curroncol30020127
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous CT-Guided Microwave Ablation Combined with Pedicle Screw Fixation Followed by Vertebroplasty (MASFVA): Initial Experience of a Minimally Invasive Treatment of Vertebral Metastases with Extension to the Vertebral Pedicle

Abstract: (1) Background: The aim of this study was to retrospectively evaluate the safety and efficacy of a combined CT-guided percutaneous microwave ablation (MWA) and pedicle screw fixation followed by vertebroplasty (MASFVA) for the treatment and stabilization of painful vertebral metastases with vertebral pedicle involvement. (2) Methods: from January 2013 to January 2017 11 patients with 16 vertebral metastatic lesions (7 men and 5 women; mean age, 65 ± 11 years) with vertebral metastases underwent CT-guided micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Minimally-invasive ablation techniques and VAPs are used in combination to reduce tumor mass, create a cavity and stabilize the vertebral body [ 28 ]. Mohme et al observed that peripheral circulating tumor cells (CTCs) are significantly increased due to vertebral cement augmentation procedures, justifying the rationale of combined ablation techniques option to reduce the increased release of CTC associated with cementoplasty [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Minimally-invasive ablation techniques and VAPs are used in combination to reduce tumor mass, create a cavity and stabilize the vertebral body [ 28 ]. Mohme et al observed that peripheral circulating tumor cells (CTCs) are significantly increased due to vertebral cement augmentation procedures, justifying the rationale of combined ablation techniques option to reduce the increased release of CTC associated with cementoplasty [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that the unopened cement components are stored at 73 °F (23 °C) for a minimum of 24 h before use. [35][36][37] This sensitivity to ambient temperature greatly impacts the injection-to-set time of the bone cement during procedures. If the ambient environment is too warm during injection, it will cause premature curing of the bone cement.…”
Section: Factors Impacting the Intraoperative Effectiveness Of Acryli...mentioning
confidence: 99%